Enhancing Mathematical Education Through Mobile Learning: A Problem-Based Approach - Javier Martínez-Gómez; Juan Francisco Nicolalde (Education Sciences)
The use of mobile phones in teaching processes, in the context of technological convergence, involves considering educational intention, pedagogical tactics, and the capacity of digital media for learning. The utilization of mobile phones in the classroom gives the students instant access to a wide range of educational resources, including educational applications, specialized websites, and multimedia material. Learning to use mobile devices responsibly and productively is essential in today’s digital age, as it prepares them for future technological interactions. The present study examines the intermediary function of a mobile education application, conceived under the problem-based learning approach, in the field of mathematics. This research was carried out with a descriptive approach. A pretest, a post-test, and a survey were created and administered for the collection of numerical data, along with an observation grid for qualitative information. The results highlight the contribution of mobile devices and problem-based learning in the development of skills for collaborative work, decision-making, and problem-solving through systems of linear equations using four techniques. The conclusions highlight the potential of mobile devices in the educational field since they are a resource that provides access to information without time or location limitations. However, it is necessary to focus on the design of pedagogical strategies to carry out a pedagogical and planned use of this resource.